2022
DOI: 10.1039/d1qi01553b
|View full text |Cite
|
Sign up to set email alerts
|

Cation substitution effects on the structural, electronic and sun-light absorption features of all-inorganic halide perovskites

Abstract: All-inorganic perovskites (such as CsPbI3) are emerging as new candidates for photovoltaic applications. Unfortunately, this class of materials present two important weaknesses in their way to commercialization: poor stability and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 114 publications
(133 reference statements)
0
2
0
1
Order By: Relevance
“…La publicación más relevante de este autor en términos de número de citas, se publicó en 2011 y fue un estudio sobre un nuevo material de banda intermedia para un mejor aprovechamiento del espectro solar (Wahnón et al, 2011). Este autor tiene una fuerte coautoría con Palacios, P. (Sánchez-Palencia et al, 2022), (Sánchez-Palencia et al, 2021, (Sánchez-Palencia et al, 2020), y con Aguilera, I. (Das et al, 2022).…”
Section: Instituciónunclassified
“…La publicación más relevante de este autor en términos de número de citas, se publicó en 2011 y fue un estudio sobre un nuevo material de banda intermedia para un mejor aprovechamiento del espectro solar (Wahnón et al, 2011). Este autor tiene una fuerte coautoría con Palacios, P. (Sánchez-Palencia et al, 2022), (Sánchez-Palencia et al, 2021, (Sánchez-Palencia et al, 2020), y con Aguilera, I. (Das et al, 2022).…”
Section: Instituciónunclassified
“…Halide perovskites have emerged as ideal materials for optoelectronic applications due to their significant absorption coefficients, high photoluminescence quantum efficiencies, tunable and direct bandgaps, long lifetimes (>1 μs), excellent charge carrier transport characteristics (∼2.6 μm diffusion length), and high tolerance to defects [1][2][3][4]. To fully explore the potential of these perovskites, the construction of perovskite heterostructures is crucial, as they constitute a vital component of modern electronics and optoelectronics, including bipolar transistors [5], light-emitting diodes [6], solar cells [7], and photodetectors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that partially substituting A-site or B-site cations in CsPbBr 3 effectively improved the quality of the CsPbBr 3 perovskite film and suppressed the charge recombination within the CsPbBr 3 perovskite film. [25][26][27][28] In addition, as we know, the B-site cations have a large effect on the valence band maximum (VBM) and conduction band minimum (CBM) of inorganic CsPbX 3 perovskites. 29 So, it is expected that partial substitution of Pb 2+ by other metal ions can simultaneously tune the bandgap and improve the quality of the CsPbBr 3 perovskite.…”
Section: Introductionmentioning
confidence: 99%